2005
DOI: 10.1002/aic.10378
|View full text |Cite
|
Sign up to set email alerts
|

PDF simulations of ethylene decomposition in tubular LDPE reactors

Abstract: The present study deals with turbulent reacting flow simulation inside low-density polyethylene (LDPE) tubular reactors, based on a detailed computational fluid dynamics (CFD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…More details of the kinetic scheme, the rate expressions, and the rate constants as well as the customized ISAT algorithm can be found in Ref. 81. The poorly mixed region is modeled using a two-dimensional axisymmetric computational domain of length 10 m and radius 1.9 cm.…”
Section: Illustrative Case Studiesmentioning
confidence: 99%
“…More details of the kinetic scheme, the rate expressions, and the rate constants as well as the customized ISAT algorithm can be found in Ref. 81. The poorly mixed region is modeled using a two-dimensional axisymmetric computational domain of length 10 m and radius 1.9 cm.…”
Section: Illustrative Case Studiesmentioning
confidence: 99%
“…[7][8][9]); and the algorithm has been incorporated into the ANSYS/FLUENT software [3,10]. ISAT has also been used in chemical engineering [11][12][13], in solid mechanics [14], control [15] and the study of thin films and surface reaction [16,17]. Several variants of ISAT have been proposed and investigated [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Here, numerical simulation methods such as computational fluid dynamics (CFD) can provide a more detailed insight into the flow conditions. In earlier publications it could be shown that the LDPE polymerization process can be modeled effectively with CFD. By adding simplified decomposition kinetics to the polymerization model , it is even possible to account for the probability of decomposition events.…”
Section: Introductionmentioning
confidence: 99%